Examining the effects of climate change and species invasions on Ontario walleye populations: can walleye beat the heat?. Issue Volume 22:Issue10(2016) (18th August 2016) - Van Zuiden, Thomas M.; Sharma, Sapna
Abstract: Aim: The combined effects of multiple environmental stressors continue to threaten global biodiversity, yet predicting how biotic interactions between native and invasive species may change across a landscape in a multiple stressor environment is relatively understudied. We aim to identify how the invasion of smallmouth bass ( Micropterus dolomeiu ) may influence native walleye ( Sander vitreus ) populations across Ontario lakes at the landscape scale in a changing climate. Location: Ontario, Canada. Methods: Using a database that included the abundance and occurrence of over 130 fish species, lake chemistry and lake morphology for 722 lakes, a redundancy analysis was conducted to identify environmental conditions preferred by walleye and smallmouth bass. Multiple linear regression models were then developed to identify the relationship between walleye and multiple stressors (including climate change and biotic interactions with invasive species). Using future scenarios of climate change, we were then able to project future walleye–smallmouth bass co‐occurrences. Results: Smallmouth bass were found to prefer different environmental conditions than walleye; however, when walleye and smallmouth bass were found in the same lakes, walleye abundance was reduced almost threefold. Multiple regression models further suggested that there are fewer walleye in lakes with smallmouth bass. Subsequently, we predicted that under future scenarios of climate change the overlapping co‐occurrence of walleye and smallmouth bass may increase by 86–332% by the year 2070. Main conclusions: We illustrate the importance of including multiple environmental stressors in statistical models when attempting to understand how native species will be impacted by invasive species and climate change. While independently climate change is anticipated to lower walleye abundances across Ontario, this change is expected to be exacerbated by invasions of warmwater predators.